48.5: Optical Measuring Methods for Transparent Displays. Issue 1 (June 2015) - Penczek, John; Kelley, Edward F.; Boynton, Paul A.
Abstract : A set of optical transmission measurements are put forth which can be used to determine the optical performance of transparent displays under arbitrary ambient lighting environments. The methodology measures the transmission coefficients in order to determine the on‐screen photometric and colorimetric characteristics of transmissive, emissive, and reflective displays. An LCD transparent display is used as an example to demonstrate these methods.